Pengaruh Non-Performing Financing Pembiayaan Mudharabah dan Murabahah terhadap Tingkat Profitabilitas Bank XXX Syariah - Zyahratul Wilda; Syahriyah Semaun; Arqam (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2020)
This study aims to determine whether there is an influence of Non-Performing Financing on mudharabah and murabaha financing on the level of profitability and want to know the dominant variables that simultaneously influence the level of profitability at the Sharia xxx Bank. This research is a quantitative research with descriptive method. Data collection is derived from financial statements. The method used to test hypotheses is to use multiple regression analysis techniques, t test, f test, coefficient of determination (R2). The results showed: Based on the results of the t test (partial) which showed that the significance value of Non-Performing Financing (NPF) mudharabah financing was -1,761 with a significance probability of 0.220 which means it was greater than the α value of 0.05, so it can be concluded that Non-Performing Financing (NPF) mudharabah financing has a negative and partially significant effect on profitability (ROA) at the Sharia xxx Bank. And the results of the t test (partial) which shows that the significance value of Non-Performing Financing (NPF) murabaha financing is 2,422 with a significance probability of 1.36 which means it is greater than the α value of 0.05, so it can be concluded that Non-Performing Financing (NPF) murabaha financing has a positive and significant effect on profitability (ROA) at the Sharia xxx Bank. And the dominant variable simultaneously influencing the level of profitability at the Sharia xxx Bank is the Performing Financing (NPF) of murabahahyakni financing at 1.36.